2023
DOI: 10.3390/children10111795
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Regulation Intervention Conducted by Teachers in a Disadvantaged School Neighborhood: Implementers’ and Observers’ Perceptions of Its Impact on Elementary Students

Jennifer Cunha,
Ana Guimarães,
Juliana Martins
et al.

Abstract: Self-regulated learning contributes to students’ academic success and their future as citizens. However, self-regulation skills are seldom or poorly promoted during instruction. To address this gap, the current article reports data on the implementation of an evidence-based intervention (i.e., a narrative-based intervention called “Yellow Trials and Tribulations”) in a disadvantaged school neighborhood. Prior studies showed positive results of this intervention in promoting elementary students’ self-regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 93 publications
2
7
0
Order By: Relevance
“…Regarding this construct, statistically significant results were found for all engagement dimensions (i.e., Hypotheses 2a-d), which is especially relevant considering that students are from a disadvantaged school neighborhood. The quantitative results retrieved from all participating students substantiate prior anecdotical qualitative findings of the implementers’ and observers’ overall perceived impact of the intervention on students ( Cunha et al, 2023 ). For instance, qualitative data ( Cunha et al, 2023 ) provided some evidence of students’ participation in session and class discussions (i.e., behavioral classroom engagement), positive emotions regarding progresses and learning (i.e., emotional classroom engagement), application of self-regulation strategies during their study (i.e., cognitive engagement), and a growing willingness to share their thoughts and opinions (i.e., agentic engagement).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Regarding this construct, statistically significant results were found for all engagement dimensions (i.e., Hypotheses 2a-d), which is especially relevant considering that students are from a disadvantaged school neighborhood. The quantitative results retrieved from all participating students substantiate prior anecdotical qualitative findings of the implementers’ and observers’ overall perceived impact of the intervention on students ( Cunha et al, 2023 ). For instance, qualitative data ( Cunha et al, 2023 ) provided some evidence of students’ participation in session and class discussions (i.e., behavioral classroom engagement), positive emotions regarding progresses and learning (i.e., emotional classroom engagement), application of self-regulation strategies during their study (i.e., cognitive engagement), and a growing willingness to share their thoughts and opinions (i.e., agentic engagement).…”
Section: Discussionsupporting
confidence: 71%
“…For this reason, the intervention was expected to help students experience choice in their actions, enthusiasm, and appreciation ( Skinner and Belmont, 1993 ; Ryan and Deci, 2020 ). Moreover, qualitative findings indicated that implementers and observers reported several examples of students who participated by sharing their opinions during intervention sessions and in class ( Cunha et al, 2023 ). However, students’ level of perceived autonomy during the intervention and the remaining instruction time (i.e., regular classes) may be different.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations